The Story of Offshore Arctic Engineering. - Masterson, Dan, 1944- (Cambridge Scholars Publishing, 2019)
In the early 1970s, new technology was needed to aid in coal, oil and gas exploration in the High Arctic, in order to see if ice sheets could provide a perfect structural support for roadways, airstrips and drilling platforms housing hundreds of workers. However, little engineering experience was available in this regard. This book uniquely relates the human history and the technical innovations developed in this harsh environment through research, testing, and applying many existing engineering principles to ice structure analysis. It offers essential insights into the history of ice engineeri.